Strategies in Media Planning - Peter Krajčovič (Communication Today, 2025)
Strategies serve as a means for achieving set objectives and goals. By selecting and applying the right strategies, many business entities have become successful on the market; they have been able to beat their competitors and face a number of risks. Therefore, business organisations may consider these strategies as a key to their successful establishment on the market. However, there are no clear definitions of such strategies; an exact ‘manual’ for selecting and implementing the ideal strategy is also hard to determine. That is why, in practice, we often come across a combination of several types of strategies. However, their common features leading to market success include the focus on thorough planning and detailed knowledge of the market. Addressing the issue of media planning, we have to take into consideration so-called media strategies or strategies of media planning. The main purpose of these strategies is to fulfil the set media objectives. It cannot be denied that media play an important role in the processes of marketing communication. They function as bearers and distributors of advertising messages which are to be delivered to the target audiences, helping the advertisers achieve their goals as well as – especially if we place emphasis on the broader contexts – related communication and marketing tasks. Therefore, we may see the media as communication tools and significant elements of advertising or communication campaigns. Selection of suitable media space is thus the basic principle of media planning and an inherent part of media strategy. The article focuses on the significance, role and position of strategies in the process of media planning; the author defines the basic types of media strategies and the main criteria for selecting the appropriate media strategy.